Introducing the non-rancidity trait into pearl millet seed : scenarios for achieving future impact in Kenya - Muindi, Pauline; Khaemba, Colleta; Rutsaert, Pieter; Donovan, Jason A.; Bandyopadhyay, Anindya; Hearne, Sarah Jane (CGIAR, 2023)
The International Maize and Wheat Improvement Center (CIMMYT) and partners are working to apply CRISPR technology to achieve a step-change in pearl millet seed product design: altering fatty acid metabolism to achieve the non-rancidity trait to create grain that when milled into flour has extended shelf life. Kenya is a country where the regulatory environment permits the introduction of gene-edited seed products when derived from site directed nuclease 1 and 2 derived technologies. Market intelligence looked to shed light on the question, If such a seed product were available in Kenya, what would be the potential relevance for millet farming and value chains? This brief explores that question by examining the context in which millet is produced, processed, and sold and the associated expectations and requirements of farmers, consumers, and processors. Data were collected through interviews with millet farmers (n=35) and rural consumers (n=35), local processors (n=14), traders (n=3), and flour producers (n=6). Value chain actors reported rancidity as a problem, but it was not perceived to be a primary challenge. Rancidity was overshadowed by larger challenges related to lack of improved seeds of any type, low production volumes, and postharvest challenges. Achieving impact from millet seed products with extended shelf life rests on changing expectations about the commercial opportunities for millet flour (such as flour-blending policies) and building viable, high performing seed systems with new varieties that address farmers’ needs, such as high yield, drought tolerance, and bird resistance. This brief concludes with future scenarios on how non-rancidity millet could deliver impact at scale.